A Pilot Study of Horizontal Head and Eye Rotations in Baseball Batting. Issue 8 (August 2017) - Fogt, Nick; Persson, Tyler W.
Abstract : PURPOSE: The purpose of the study was to measure and compare horizontal head and eye tracking movements as baseball batters "took" pitches and swung at baseball pitches. METHODS: Two former college baseball players were tested in two conditions. A pitching machine was used to project tennis balls toward the subjects. In the first condition, subjects acted as if they were taking (i.e., not swinging) the pitches. In the second condition, subjects attempted to bat the pitched balls. Head movements were measured with an inertial sensor; eye movements were measured with a video eye tracker. RESULTS: For each condition, the relationship between the horizontal head and eye rotations was similar for the two subjects, as were the overall head-, eye-, and gaze-tracking strategies. In the "take" condition, head movements in the direction of the ball were larger than eye movements for much of the pitch trajectory. Large eye movements occurred only late in the pitch trajectory. Gaze was directed near the ball until approximately 150 milliseconds before the ball arrived at the batter, at which time gaze was directed ahead of the ball to a location near that occupied when the ball crosses the plate. In the "swing" condition, head movements in the direction of the ball were larger than eye movements throughout the pitch trajectory. Gaze was directed near the ball until approximately 50 to 60 milliseconds prior to pitch arrival at the batter. DISCUSSION: Horizontal head rotations were larger than horizontal eye rotations in both the "take" and "swing" conditions. Gaze was directed ahead of the ball late in the pitch trajectory in the "take" condition, whereas gaze was directed near the ball throughout much of the pitch trajectory in the "swing" condition.